Development and evolution of Islamic schools of thought - Zabidi, Nur Ain Amalin; Mohd Rizal, Maisarah Izzah Hazwani; Abdul Rahim, Wan Norsyazwanie Wan; Mat, Nur Insyira (2025)
This study discusses the development and evolution of Islamic schools of thought, which include aspects of fiqh, aqidah, and tasawuf. Development refers to how these schools of thought began and continue to develop over time, while evolution shows how these schools of thought adapt to changes in time, place, and social conditions. The diversity of views within a school is not a form of opposition, but rather a blessing that shows the flexibility and dynamism of Islamic teachings in facing the realities of life. This study aims to identify the basic concepts of the development and evolution of Islamic schools of thought, analyze the factors that contribute to the advancement of Islamic thought and civilization, and evaluate the impact of these changes. The methodology of this study is based on content analysis from authentic scientific journals and articles. Overall, the findings of this study found that the development and change of Islamic schools of thought is a form of Fiqh al-Muqaran knowledge that examines the diversity of laws and the views of mujtahids from the main schools of thought in Islam. With this study, it is hoped that readers can open their eyes in deepening their knowledge about the diversity of schools of thought and not view other schools as a mistake. Understanding and appreciating the views of each different school of thought according to the development and changes of the times is very important among Muslims. Therefore, this study also makes an important contribution in educating the community about the beauty and wisdom behind the diversity of laws in the four main schools of thought that remain relevant throughout the ages.